2014
DOI: 10.1039/c4cc02947j
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-catalyzed intramolecular annulation via C–H activation leading to fused tricyclic indole scaffolds

Abstract: The rhodium(III)-catalyzed intramolecular annulation of alkyne-tethered acetanilides for the synthesis of fused tricyclic indole scaffolds via C-H activation has been developed, which has the potential for the synthesis of many indole alkaloids. This reaction proceeds under mild reaction conditions and with tolerance to a variety of functional groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(15 citation statements)
references
References 42 publications
0
14
1
Order By: Relevance
“…This unique chemistry for indole makes it a potent and promising building block for various biological applications, notably for drug development. [36][37][38][39] In this context, indole has been used to develop fluorescent conjugates [40] and for sensing a wide range of analytes such as anions [41,42] , more importantly acetate [43,44] , fluoride [45] , cyanide [46] , and iodide. [47]…”
Section: Indoles In Sensing Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…This unique chemistry for indole makes it a potent and promising building block for various biological applications, notably for drug development. [36][37][38][39] In this context, indole has been used to develop fluorescent conjugates [40] and for sensing a wide range of analytes such as anions [41,42] , more importantly acetate [43,44] , fluoride [45] , cyanide [46] , and iodide. [47]…”
Section: Indoles In Sensing Systemsmentioning
confidence: 99%
“…In addition, indole molecules are reactive against strong acids due to their weak basic nature, therefore they undergo N‐substitution under basic conditions through the slightly acidic N–H bond. This unique chemistry for indole makes it a potent and promising building block for various biological applications, notably for drug development . In this context, indole has been used to develop fluorescent conjugates and for sensing a wide range of analytes such as anions, more importantly acetate, fluoride, cyanide, and iodide …”
Section: Introductionmentioning
confidence: 99%
“…In 2014, the groups of Liu, Jia and Li reported independently the intramolecular amidoarylation of alkyne catalyzed by Cp*Rh III complexes. The authors showed that a series of 3,4‐fused tricyclic indoles could be obtained in moderate to excellent yields under mild oxidative conditions [Cu(OAc) 2 · H 2 O under O 2 ], in the presence of [Cp*Rh(MeCN) 3 ][SbF 6 ] 2 or [Cp*RhCl 2 ] 2 in acetone or t ‐AmOH (Scheme ).…”
Section: Intramolecular Coupling With Alkynesmentioning
confidence: 99%
“…In a related study, the same group showed that macrocyclic 3,5‐fused indoles 37a – e could be obtained from para ‐substituted acetanilides 36a – e . (Scheme ).…”
Section: Intramolecular Coupling With Alkynesmentioning
confidence: 99%
“…Almost at the same time, Jia reported the intramolecular synthesis of tricyclic indoles through a similar strategy (Scheme 15). 20 In the presence of be smoothly converted to the corresponding tricyclic indoles at room temperature under an O 2 atmosphere. Both 3,4-fused indoles and 3,5-macrocycle indoles could be synthesized in moderate yields under the standard conditions.…”
Section: Anilidesmentioning
confidence: 99%